Seismotectonics and rupture process of the MW 7.1 2011 Van reverse-faulting earthquake, eastern Turkey, and implications for hazard in regions of distributed shortening. Issue 1 (20th April 2016) - Mackenzie, D.; Elliott, J.R.; Altunel, E.; Walker, R.T.; Kurban, Y.C.; Schwenninger, J.-L.; Parsons, B.
Abstract: The 2011 October 23 M W 7.1 Van earthquake in eastern Turkey caused ∼600 deaths and caused widespread damage and economic loss. The seismogenic rupture was restricted to 10–25 km in depth, but aseismic surface creep, coincident with outcrop fault exposures, was observed in the hours to months after the earthquake. We combine observations from radar interferometry, seismology, geomorphology and Quaternary dating to investigate the geological slip rate and seismotectonic context of the Van earthquake, and assess the implications for continuing seismic hazard in the region. Transient post-seismic slip on the upper Van fault started immediately following the earthquake, and decayed over a period of weeks; it may not fully account for our long-term surface slip-rate estimate of ≥0.5 mm yr −1 . Post-seismic slip on the Bostaniçi splay fault initiated several days to weeks after the main shock, and we infer that it may have followed the M W  5.9 aftershock on the 9th November. The Van earthquake shows that updip segmentation can be important in arresting seismic ruptures on dip-slip faults. Two large, shallow aftershocks show that the upper 10 km of crust can sustain significant earthquakes, and significant slip is observed to have reached the surface in the late Quaternary, so there may be a continuing seismic hazard from the upper Van fault and the associated splay. The wavelength of folding in the hanging wall of the Van fault is dominated by the structure in the upper 10 km of the crust, masking the effect of deeper seismogenic structures. Thus, models of subsurface faulting based solely on surface folding and faulting in regions of reverse faulting may underestimate the full depth extent of seismogenic structures in the region. In measuring the cumulative post-seismic offsets to anthropogenic structures, we show that Structure-from-Motion can be rapidly deployed to create snapshots of post-seismic displacement. We also demonstrate the utility of declassified Corona mission imagery (1960s–1970s) for geomorphic mapping in areas where recent urbanization has concealed the geomorphic markers.